NANOSUSPENSION: AN OVERVIEW - Aher, Smita S.; Malsane, Sagar T.; Saudagar, R. B. (International Journal of Current Pharmaceutical Research, 2017)
Nanosuspensions are important carriers to develop novel drug formulations. Nanosuspensions have emerged as a promising strategy for the efficient delivery of hydrophobic drugs because of their versatile features and unique advantages. Nanosuspension technology solved the problem of drugs which are poorly aqueous soluble and less bioavailability. Stability and bioavailability of the drugs can be improved by the Nanosuspension technology. Techniques such as media milling and high-pressure homogenization have been used commercially for producing nanosuspensions. Nanosuspensions can be delivered by oral, parenteral, pulmonary and ocular routes. Nanosuspensions can also be used for targeted drug delivery when incorporated in theOcular inserts and mucoadhesive hydrogels. Currently, efforts are being directed to extending their applications in site-specific drug delivery.